KEPASTIAN HUKUM PENGAWASAN KOPERASI TERKAIT KESALAHAN PENGELOLAAN KOPERASI DAN TANGGUNG JAWABNYA. - Irawan, Cendy; Martien, Dhoni; Ismed, Mohamad (LPPM Institut Pendidikan Nusantara Global, 2024)
The duties of the Cooperative Supervisor include supervising the implementation of the policy and management of the Cooperative, with the duties attached to his position, of course the Cooperative Supervisor can prevent any form of deviation in the management of the Cooperative's business to achieve the objectives of the Cooperative. In reality, not a few of the Cooperatives experienced mismanagement of the Cooperative's business which resulted in the failure of the refund of Members deposits by the Cooperative. The mismanagement of the Cooperative's business has a correlation with the Cooperative's internal supervisory function. The formulation of the problem in this research is how is the responsibility of the Cooperative Supervisor related to the mismanagement of the Cooperative? and How is the legal position of the Cooperative Supervisor related to the mismanagement of the Cooperative? The theories used as an analytical tool in this research are legal certainty and legal liability. The method used in this research is normative juridical research, namely library legal research or secondary data with primary, secondary and tertiary legal sources. The research approach used is a statutory approach, case approach, conceptual approach and analytical approach, with legal material collection techniques carried out by identifying and inventorying positive legal rules, book literature, journals and other sources of legal material. For legal material analysis techniques carried out by systematic interpretation and teleological interpretation. From the results of the research, it can be concluded that in supervising the implementation of the policy and management of the Cooperative, the Cooperative Supervisor is responsible to the Members' Meeting. The Cooperative Supervisor can be held accountable in the event of mismanagement of the Cooperative business due to his actions. The position of the Cooperative Supervisor is regulated in Article 21 of Law No. 25 of 1992 in conjunction with Article 21 of Law No. 6 of 2023. Suggestions in this study are that the Cooperative Supervisor should have a sense of responsibility and be professional in carrying out his duties and the Government together with the Indonesian House of Representatives must immediately revise Law No. 25 of 1992 or Law No. 6 of 2023 or form a new Cooperative Law by including provisions on sanctions and benchmarks or the scope of duties of the Cooperative Supervisor